Ocean acidification effects on marine microbial communities - Krause, Evamaria (PLoS ONE, 2013)
Anthropogenic CO2 emissions are causing an acidification of the world’s oceans. The consequences for marine organisms and especially heterotrophic bacteria remain under debate, and almost nothing is known concerning marine fungi. Both microbial groups are important players in organic matter decomposition and nutrient cycling, and their pH tolerance is known to be broad in relation to the predicted acidification. So far, ocean acidification effects on marine bacterial communities have mainly been investigated in large-scale mesocosm studies. In these systems, indirect effects mediated through complex food web interactions come into play. Until now, these experiments were not carried out in sufficient replication. In this thesis, we chose an alternative approach and investigated bacterial and fungal communities in highly replicated microcosm experiments (1-1.6 L). The duration of the experiments was four weeks. We incubated the natural microbial community from Helgoland Roads (North Sea) at in situ seawater pH, pH 7.82 and pH 7.67. These pH levels represent the present-day situation and acidification at atmospheric CO2 of 700 or 1000 ppm, projected for the southern North Sea for the year 2100. For the bacterial community, different dilution approaches were used to select for different ecological groups. Seasonality was accounted for by repeating the experiment four times (spring, summer, autumn, winter). In a second experiment repeated in two consecutive years, we investigated direct pH effects on marine fungal communities. We additionally isolated marine yeasts and identified them by Matrix-assisted laser desorption/ionization-time-of-flight mass spectrometry (MALDI-TOF MS) and partial sequencing of the large subunit (LSU) rRNA gene. To reveal changes in community structure, we applied the culture-independent fingerprint method automated ribosomal intergenic spacer analysis (ARISA) for both bacteria and fungi. Bacterial communities were furthermore analyzed by 16S ribosomal amplicon pyrosequencing. Abundances ...